Nutrient cycling aspects in stands of Pinus-elliottii engelm var elliottii under differents resining intensities .2. nutrients contents in litter - Soave, RDF; Pagano, S. N. (Inst Tecnologia Parana, 1994)
Annual and monthly quantities of nutrients wich returned to the soil through litter fall in Pinus elliottii Engelm. var. elliottii stand were estimated durint a two years period, in Experimental Station of Mogi-Guacu, SP. From the trees of the stand was extracted oleoresin according two differents techniques and control. The annual average of nutrients that returned to the soil was 72.2 Kg/ha, in following order: N > Ca > K > Mg > P. No relationship appeared between nutrient concentrations plus quantities when they were compared with oleoresin yields treatments and control. The differences in annual quantities were possibly due to climatic factors. The soil profile showed short concentrations in nutrient contents. Thus, the forest may be suffering by nutrient deficiences.
Keywords: NUTRIENTS; CYCLING; LITTER FALL; OLEORESIN; PINUS-ELLIOTTII